Inside Front Cover: Selective and sensitive Escherichia coli detection based on a T4 bacteriophage‐immobilized multimode microfiber (J. Biophotonics 9/2018). Issue 9 (6th September 2018) - Li, Yanpeng; Ma, Hui; Gan, Lin; Gong, Andong; Zhang, Haibin; Liu, Deming; Sun, Qizhen
Abstract : Sensitive Escherichia coli detection based on a T4 bacteriophageimmobilized multimode microfiber is proposed and demonstrated in this article. Different modes are excited and guided in the microfiber as evanescent field that can interact with surrounding E. coli directly. The change of E. coli concentration and corresponding binding of E. coli on microfiber surface will lead to the shift of optical spectrum, which can be exploited for the application of biosensing. Further details can be found in the article by Yanpeng Li, Hui Ma, Lin Gan, et al. (e201800012 ). Abstract : Sensitive Escherichia coli detection based on a T4 bacteriophageimmobilized multimode microfiber is proposed and demonstrated in this article. Different modes are excited and guided in the microfiber as evanescent field that can interact with surrounding E. coli directly. The change of E. coli concentration and corresponding binding of E. coli on microfiber surface will lead to the shift of optical spectrum, which can be exploited for the application of biosensing. Further details can be found in the article by Yanpeng Li, Hui Ma, Lin Gan, et al. (e201800012 ).